2009
DOI: 10.1111/j.1469-7610.2008.02033.x
|View full text |Cite
|
Sign up to set email alerts
|

Is neurofeedback an efficacious treatment for ADHD? A randomised controlled clinical trial

Abstract: Background: For children with attention deficit/hyperactivity disorder (ADHD), a reduction of inattention, impulsivity and hyperactivity by neurofeedback (NF) has been reported in several studies. But so far, unspecific training effects have not been adequately controlled for and/or studies do not provide sufficient statistical power. To overcome these methodological shortcomings we evaluated the clinical efficacy of neurofeedback in children with ADHD in a multisite randomised controlled study using a compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
350
1
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 337 publications
(374 citation statements)
references
References 30 publications
(37 reference statements)
17
350
1
6
Order By: Relevance
“…The 3 studies comparing NF to computerized attention skills training (CAST) yielded conflicting results. The largest study so far (including 94 individuals) found NF to be superior to CAST [39]. One study found no significant difference between groups, although only the NF group improved in relation to baseline, and the lack of difference may be due to the low power provided by the small sample sizes [53].…”
Section: Brain Electric Activity and Its Relation To Brain Functionmentioning
confidence: 98%
See 4 more Smart Citations
“…The 3 studies comparing NF to computerized attention skills training (CAST) yielded conflicting results. The largest study so far (including 94 individuals) found NF to be superior to CAST [39]. One study found no significant difference between groups, although only the NF group improved in relation to baseline, and the lack of difference may be due to the low power provided by the small sample sizes [53].…”
Section: Brain Electric Activity and Its Relation To Brain Functionmentioning
confidence: 98%
“…In addition, from the 8th session onward, patients had to practice their strategy to remain "activated" for at least 10 minutes a day on some daily life task that require them to be attentive like doing the homework or playing a game. Children were instructed to identify situations in which these strategies would be important and to increase their attention control strategies [39]. In conclusion, available data suggest that NF is effective long-term, but it is possible that the long-term effects of NF depend on the generalization of regulatory skills to daily life.…”
Section: Is Long-term Nf Effective?mentioning
confidence: 99%
See 3 more Smart Citations